2021
DOI: 10.1002/adsc.202100991
|View full text |Cite
|
Sign up to set email alerts
|

Iodine‐Catalyzed Double [4+2] Oxidative Annulations for the Synthesis of Bipyrazines from Ketones and Diamines by a Domino Strategy

Abstract: An iodine-catalyzed double [4 + 2] oxidative annulation of ketones and diamines is described. A multi-pathway coupled domino strategy has been developed for the synthesis of substituted dimeric pyrazines under metal-free conditions. One CÀ C and four CÀ N bonds are formed during this double [4 + 2] oxidative annulation process from two ketones and two diamines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Subsequently, deprotonation of intermediate 11 affords intermediate 12 , which is detected by GC–MS (see Figure S2). Finally, the desired product 3a is obtained from intermediate 12 through an aerial oxidation procedure using oxygen as the green oxidant …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, deprotonation of intermediate 11 affords intermediate 12 , which is detected by GC–MS (see Figure S2). Finally, the desired product 3a is obtained from intermediate 12 through an aerial oxidation procedure using oxygen as the green oxidant …”
Section: Resultsmentioning
confidence: 99%
“…Finally, the desired product 3a is obtained from intermediate 12 through an aerial oxidation procedure using oxygen as the green oxidant. 40…”
Section: The Journal Of Organicmentioning
confidence: 99%
“…Spiro-2,3-dihydrobenzofuran is a prominent structural skeleton, which ubiquitously exists in many medicinal and natural products. 1 Examples include griseofulvin, 2 furaquinocin A 3 and corallidictyal D. 4 Moreover, there are also several biologically active dihydrobenzofuran cores, including stachybotrylactam which is used as the HIV-1 protease inhibitor 5 and XEN907 which is used as the hNav1.7 blocker. 6 Thus, several methods have been developed for the synthesis of these skeletons, such as [4 + 1] cycloaddition reaction 5,7 and dearomatization of benzofurans.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, using benzene-1,2-diamines as 1,4-dinucleophiles, cascade functionalization and C–N bond cleavage of cyclic amines selectively occurs to afford difunctionalized acyclic amines 3-(quinoxalin-2-yl)propan-1-amines based on β-oxo cyclic iminium ion intermediates (Scheme 1(B)). Bearing in mind the importance of both functionalized alicyclic amines 1 and 2-substituted quinoxalines, 12 we made a detailed study of this aspect.…”
mentioning
confidence: 99%
“…and KSCN (1 equiv.) in DMF at rt under air for 6 h. Considering the importance of functionalized quinoxaline, 12 the suitability of different N -aryl piperidines 1 in this conversion was investigated. It showed that substrates 1 bearing an electron-donating group (Me) or an electron-withdrawing group (F, Cl or Br) attached at the ortho -, meta - or para -position of the aryl moiety were compatible for this reaction and afforded 5b–5k in moderate to good yields (50–74%).…”
mentioning
confidence: 99%